Static and Dynamic Recidivism Risk Factors of People Who Have Committed Child Sex Offenses in Sport - Vertommen, Tine; Verhelle, Helena; Martijn, Frederica M.; De Boeck, Minne (Frontiers in Sports and Active Living, 2021)
Current knowledge of people who commit child sex offenses (PCSO) in sport contexts is based on descriptive information from cross-sectional self-report studies of survivors and media coverage of court cases. In-depth scientific analyses of characteristics, interpersonal dynamics, and applied theories of sexual offending in sport are largely absent. This paper starts with a description of available Belgian data on PCSO in sport, coming from self-reports in community samples, reported cases in the media, and interviews with survivors. The main goal of this study is the analysis of treatment file information from 16 convicted PCSO in sport using two actuarial recidivism assessment instruments (STATIC-99R and STABLE-2007). Overall, the majority of the included PCSO's risk assessments indicated relatively low risk of sexual recidivism. Notable was the preponderance of high risk scores on items related to exclusively unrelated victims, male victims, sexual deviance, and the absence of an intimate relationship. Other static and dynamic factors related to the risk of sexual recidivism, e.g., (prior) non-sexual violent offenses, unknown victims, hostility toward women, lack of concern for others, and poor cooperation with supervisors were rated relatively low in this sample of PCSO in sport. The findings point toward the complex and nuanced patterns that underlie child sexual abuse in sport. The current findings bring us one step closer to filling in the puzzle of child sexual abuse in sport and will help inform evidence- and experience-based prevention and intervention efforts.